A newly identified single nucleotide polymorphism in the promoter of the matrix metalloproteinase-1 gene - Jurajda, M; Muzík, J; Izakovicová Hollá, L; Vácha, J (Molecular and cellular probes, 2002)
Matrix metalloproteinase-1 (MMP-1) is a member of the matrix metalloproteinase enzyme family that degrades components of the extracellular matrix. Recent studies have demonstrated several polymorphic sites in the promoter of the MMP-1 gene. A newly identified single nucleotide polymorphism (SNP) at position -519 in the promoter region of the MMP-1 gene is reported. This polymorphism consists in a guanine to adenine substitution. A linkage between polymorphisms -519A/G and -1607 1G/2G was also studied.
Keywords: senioři; běloši; jednonukleotidový polymorfismus; kolorektální nádory; Česká republika; Middle Aged; Promoter Regions, Genetic; Colorectal Neoplasms; mužské pohlaví; Matrix Metalloproteinase 1; Adult; Czech Republic; ženské pohlaví; Humans; Binding Sites; matrixová metaloproteinasa 1; lidé středního věku; frekvence genu; promotorové oblasti (genetika); White People; Gene Frequency; dospělí; Female; Aged; vazebná místa; lidé; Male; Polymorphism, Single Nucleotide